Studying the Impacts of Inflation, Import and Export on Gross Domestic Product using Markov Switching Vector Autoregressive Model - Micheal, V. A.; Adenomon, M. O. (Benin Journal of Statistics, 2022)
Some macroeconomic variables have been studied based on their impacts and contribution to the economic growth especially in Nigeria. The study focuses on the impacts of inflation, import and export on the gross domestic product using Markov switching vector autoregressive(MS-VAR) model which is designed for econometric modeling of univariate and multiple time series subject to shifts in regime. The data spanned through 1980 to 2020 from National Bureau of Statistics and Central Bank of Nigeria respectively. The result of ADF test and Philip Perron test showed that the variables are stationary at first difference I(1) at 5% critical value. The Zivot-Andrew unit root with structural break showed that the variables are also integrated of order 1. The respective dates correspond to transition of government in 1983, structural adjustment programme in 1986, election in 1993 and a coup in 1995. Inflation is statistically significant using Lee-Strazicich test for two structural breaks. The results of cointegration test indicated that there is no long run relationship among the variables of interest without and with structural breaks. MS-VAR result showed that the probability of staying in regime 1 (that is a period of expansion) in Nigeria economy is higher than in regime 2 (that is a period or state of recession) in the nation’s economy which suggests that regime 1 is more persistent than regime 2 and the period of growth in regime 1 is about 16 years while it lasted 11 years in regime 2. This implies that Nigeria economy is more stable in regime 1(expansion period) compared to that of regime 2.